2022
DOI: 10.1038/s41598-022-13285-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the usefulness of non-invasive serum haemoglobin measurement in a perioperative setting in a prospective observational study

Abstract: Patient Blood Management (PBM) programmes seek to reduce the number of missed anaemic patients in the run-up to surgery. The aim of this study was to evaluate the usefulness of haemoglobin (Hb) measured non-invasively (SpHb) in preoperative screening for anaemia. We conducted a prospective observational study in a preoperative clinic. Adult patients undergoing examination for surgery who had their Hb measured by laboratory means also had their Hb measured non-invasively by a trained health care provider. 1216 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The SpHb sensitivity varies between different studies. In Khalafallah et al's RCT study (2015) and Wittenmeier et al's prospective study (2021), both groups reported adequate SpHb and adequate sensitivity [10,12] in contrast with Honnef G et al's study (2022), an observational study, which reported lower SpHb sensitivity, similar to our findings [11].…”
Section: Sphb-hb Relationship Variationssupporting
confidence: 86%
See 1 more Smart Citation
“…The SpHb sensitivity varies between different studies. In Khalafallah et al's RCT study (2015) and Wittenmeier et al's prospective study (2021), both groups reported adequate SpHb and adequate sensitivity [10,12] in contrast with Honnef G et al's study (2022), an observational study, which reported lower SpHb sensitivity, similar to our findings [11].…”
Section: Sphb-hb Relationship Variationssupporting
confidence: 86%
“…Variations in accuracy between these devices are still the focus of debates [10][11][12][13][14][15], and there are a few recently published studies examining patients with SCD [8,16].…”
Section: Introductionmentioning
confidence: 99%
“…Khalafallah et al, in their RCT (2015), reported an increase in the SpHb accuracy (sensitivity) at low Hb values for males compared to females. Honnef et al (2022), in an observational study, reported that the sensitivity of SpHb to identify anemia was low, in contrast to the prospective study by Wittenmeier et al (2021) [9][10][11]. This diversity between various researchers motivated our team to design this current research to study the Masimo Radical-7 performance as a non-invasive hemoglobin monitor.…”
Section: Introductionmentioning
confidence: 98%
“…Early works on PPG demonstrated that detecting transmitted or re ected light from a ngertip allows to determine Hb level by analysing the oscillating component of diffuse re ection associated with blood pulsation [10]. However, although a number of studies reported results with an error of less than 10 g/l [7,8], independent prospective studies show that even the FDAcerti ed devices have a high measurement error exceeding 15-20 g/l and have a low sensitivity in detecting anaemia [3,11,12]. Namely, some works report sensitivity of detecting a low Hb level using PPG to be ~0.4-0.5 [3,11]; other studies report the detection of a low Hb level with a sensitivity of about 0.8 [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, although a number of studies reported results with an error of less than 10 g/l [7,8], independent prospective studies show that even the FDAcerti ed devices have a high measurement error exceeding 15-20 g/l and have a low sensitivity in detecting anaemia [3,11,12]. Namely, some works report sensitivity of detecting a low Hb level using PPG to be ~0.4-0.5 [3,11]; other studies report the detection of a low Hb level with a sensitivity of about 0.8 [13]. Sensitivity of the prediction of low Hb level in newborns was reported to be in the 0.7-0.9 range [14], while the speci city of the PPG (in prediction of normal Hb level) is generally higher (0.8-0.9).…”
Section: Introductionmentioning
confidence: 99%